Acute myocardial infarction therapy using calycosin and tanshinone co-loaded; mitochondrion-targeted tetrapeptide and cyclic arginyl-glycyl-aspartic acid peptide co-modified lipid-polymer hybrid nano-system: preparation, characterization, and anti myocardial infarction activity assessment. (31st December 2022) - Yan, Jieke; Guo, Jing; Wang, Yuzhen; Xing, Xiaowei; Zhang, Xuguang; Zhang, Guanghao; Dong, Zhaoqiang
Abstract: Acute myocardial infarction (AMI) is one of the most common ischemic heart diseases. However, lack of sufficient drug concentration (in the ischemic heart) is the major factor of treatment failure. It is urgent for researchers to engineer novel drug delivery systems to enhance the targeted delivery of cardioprotective agents. The aim of the present study was to investigate the anti-AMI ability of calycosin (CAL) and tanshinone (TAN) co-loaded; mitochondrion-targeted tetrapeptide (MTP) and cyclic arginyl-glycyl-aspartic acid (RGD) peptide co-modified nano-system.: We prepared CAL and TAN combined lipid-polymer hybrid nano-system, and RGD was modified to the system to achieve RGD-CAL/TAN NS. MTP-131 was conjugated with PEG and modified onto the nanoparticles to achieve dual ligands co-modified MTP/RGD-CAL/TAN NS. The physicochemical properties of nano-systems were characterized. The AMI therapy ability of the systems was investigated in AMI rats' model. The size of MTP/RGD-CAL/TAN NS was 170.2 ± 5.6 nm, with a surface charge of −18.9 ± 1.9 mV. The area under the curve (AUC) and blood circulation half-life (T1/2 ) of MTP/RGD-CAL/TAN NS was 178.86 ± 6.62 μg·min/mL and 0.47 h, respectively. MTP/RGD-CAL/TAN NS exhibited the most significant infarct size reduction effect of 22.9%. MTP/RGD-CAL/TAN NS exhibited the highest heart accumulation and best infarct size reduction effect, which could be used as a promising system for efficient treatment of cardiovascular diseases.